2011
DOI: 10.1073/pnas.1105941108
|View full text |Cite
|
Sign up to set email alerts
|

Selective killing of K-ras mutant cancer cells by small molecule inducers of oxidative stress

Abstract: Activating K-RAS mutations are the most frequent oncogenic mutations in human cancer. Numerous downstream signaling pathways have been shown to be deregulated by oncogenic K-ras. However, to date there are still no effective targeted therapies for this genetically defined subset of patients. Here we report the results of a small molecule, synthetic lethal screen using mouse embryonic fibroblasts derived from a mouse model harboring a conditional oncogenic K-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
160
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(167 citation statements)
references
References 33 publications
4
160
1
2
Order By: Relevance
“…This causes the down-regulation of growth-promoting signals from tyrosine kinase receptors and this may be the mechanism by which ROS impair growth. In support of this antiproliferative role of ROS, two studies have identified two different ROSinducing compounds from chemical screens that can inhibit the growth of KRAS-transformed 3T3 cells (19) and cancer cells (20). In addition, it was recently shown that the transcription factor Nrf2 (which controls a antioxidant pathway) was required for tumorigenesis in mice by oncogenes such as Kras (21).…”
Section: Discussionmentioning
confidence: 99%
“…This causes the down-regulation of growth-promoting signals from tyrosine kinase receptors and this may be the mechanism by which ROS impair growth. In support of this antiproliferative role of ROS, two studies have identified two different ROSinducing compounds from chemical screens that can inhibit the growth of KRAS-transformed 3T3 cells (19) and cancer cells (20). In addition, it was recently shown that the transcription factor Nrf2 (which controls a antioxidant pathway) was required for tumorigenesis in mice by oncogenes such as Kras (21).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, lanperisone also showed efficacy against tumor growth in a K-Ras-driven mouse model of lung cancer. 12 The exact mechanism responsible for lanperisone-induced ROS generation is not known, but preliminary results suggest that it occurs through the perturbation of voltage-gated ion channels. 11 Sulfasalazine.…”
Section: Morphologymentioning
confidence: 99%
“…Nevertheless, limited efforts have been dedicated to dissect the role of combinations of mutations in determining drug response. Among these studies, it is worth mentioning the use of isogenic cell lines to evaluate the influence of KRAS or TP53 status on the sensitivity to (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%